2012
DOI: 10.1093/ndt/gfr773
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin free light chain levels and recovery from myeloma kidney on treatment with chemotherapy and high cut-off haemodialysis

Abstract: The combination of extended HCO-HD and chemotherapy resulted in sustained reductions in serum FLC concentrations in the majority of patients and a high rate of independence of dialysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
91
0
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(107 citation statements)
references
References 16 publications
9
91
0
7
Order By: Relevance
“…This is an important observation, given that earlier data, in smaller numbers of patients, suggested that only about a third of patients could discontinue dialysis [12][13][14][15]. Our results should be carefully compared to the results obtained with the use of HCO dialysis, since with extended HCO dialysis up to 70% may become dialysis independent [16,17]. The results of the prospective randomized trials (EuLITE, NCT00700531 and MYRE, NCT01208818) will define the role of mechanical means for the management of patients with MM and cast nephropathy requiring dialysis, but, in both studies, VD-based therapy is the backbone.…”
Section: Discussionmentioning
confidence: 55%
“…This is an important observation, given that earlier data, in smaller numbers of patients, suggested that only about a third of patients could discontinue dialysis [12][13][14][15]. Our results should be carefully compared to the results obtained with the use of HCO dialysis, since with extended HCO dialysis up to 70% may become dialysis independent [16,17]. The results of the prospective randomized trials (EuLITE, NCT00700531 and MYRE, NCT01208818) will define the role of mechanical means for the management of patients with MM and cast nephropathy requiring dialysis, but, in both studies, VD-based therapy is the backbone.…”
Section: Discussionmentioning
confidence: 55%
“…One such approach involves the use of extended dialysis sessions for patients with myeloma cast nephropathy using a dialyzer cartridge with pores of sufficient size to allow the removal of light chains. Pooling data from multiple centers, Hutchison et al (57,94) showed that nearly three quarters of dialysis-dependent patients receiving this therapy recover renal function and that this recovery is predicted by the degree of light chain reduction and a shorter time between presentation and initiation of light chain-removing dialysis (94 …”
Section: Plasmapheresis and Other Extracorporeal Techniques To Removementioning
confidence: 99%
“…In a previous investigation of myeloma patients presenting with AKI at diagnosis who underwent a renal biopsy, the principal pathology in nearly 90% of patients was cast nephropathy as a consequence of excess and nephrotoxic monoclonal FLCs [25]. Therefore, myeloma patients with severely reduced kidney function present with high sFLC levels as the direct cause in almost all cases.…”
Section: Discussionmentioning
confidence: 97%